Risk factors for postoperative myasthenia gravis in patients with thymoma without myasthenia gravis: A systematic review and meta-analysis - Tang, Mingbo; Shao, Yifeng; Dong, Junxue; Gao, Xinliang; Wei, Shixiong; Ma, Jianzun; Hong, Yang; Li, Zhiqin; Bi, Taiyu; Yin, Yipeng; Zhang, Wenyu; Liu, Wei (Frontiers in Oncology, 2023)
Introduction According to the principle, thymomas combined with myasthenia gravis (MG) require surgical treatment. However, patients with non-MG thymoma rarely develop MG and early- or late-onset MG after surgery is called postoperative MG (PMG). Our study used a meta-analysis to examine the incidence of PMG and risk factors. Methods Relevant studies were searched for in the PubMed, EMBASE, Web of Science, CNKI,and Wanfang databases. Investigations that directly or indirectly analyzed the risk factors for PMG development in patients with non-MG thymoma were included in this study. Furthermore, risk ratios (RR) with 95% confidence intervals (CI) were pooled using meta-analysis, and fixed-effects or random-effects models were used depending on the heterogeneity of the included studies. Results Thirteen cohorts containing 2,448 patients that met the inclusion criteria were included. Metaanalysis revealed that the incidence of PMG in preoperative patients with non-MG thymoma was 8%. Preoperative seropositive acetylcholine receptor antibody (AChR-Ab) (RR = 5.53, 95% CI 2.36 – 12.96, P<0.001), open thymectomy (RR =1.84, 95% CI 1.39 – 2.43, P<0.001), non-R0 resection (RR = 1.87, 95% CI 1.36 – 2.54, P<0.001), world health organization (WHO) type B (RR =1.80, 95% CI 1.07 – 3.04, P= 0.028), and postoperative inflammation (RR = 1.63, 95% CI 1.26 – 2.12, P<0.001) were the risk factors for PMG in patients with thymoma. Masaoka stage (P = 0.151) and sex (P = 0.777) were not significantly associated with PMG. Discussion Patients with thymoma but without MG had a high probability of developing PMG. Although the incidence of PMG was very low, thymectomy could not completely prevent the occurrence of MG. Preoperative seropositive AChR-Ab level, open thymectomy, non-R0 resection, WHO type B, and postoperative inflammation were risk factors for PMG. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022360002.